Kemampuan Kompetensi Guru dan Motivasi Belajar Siswa Terhadap Peningkatan Hasil Belajar Siswa SDN 012 Lalang Kabung Kabupaten Pelalawan - Lestari, Afdhal; Alim, Jesi Alexander; Putra, Zetra Hainul (Indonesian Journal of Science, Technology, Engineering, Art, and Mathematics Education, 2023)
This study aims to analyze the influence of teacher competence, motivation and student learning outcomes at SDN 012 Lalang Kabung, Pelalawan Regency. This study uses a quantitative approach using path analysis. Data collection techniques are questionnaires and documentation. The data analysis technique used is explanatory survey analysis. The sample in this study were 20 grade VI elementary school students. The results of this study indicate that there is a positive and significant influence between teacher competence on student learning outcomes as a whole, there is a positive and significant influence between student learning motivation on student learning outcomes as a whole. So it was concluded that indirectly motivation through job satisfaction has a significant effect on teacher performance (H3 Accepted). Meanwhile, the indirect effect of teacher competence on learning outcomes is the multiplication of the beta value (learning motivation on learning outcomes) and the beta value (job satisfaction on teacher performance), namely 0.565 x 0.979 = 0.553. Based on the calculation above, it is known that the direct effect is 0.565 and the indirect effect is 0.979. So it means that the indirect influence is greater than the direct influence. So it is concluded that indirectly the work environment has a significant effect on teacher performance (H4 Rejected).